Atrioventricular pacemaker. Incidence and causes of reprogramming in long-term follow-up - Martinelli Fº,Martino (2001)
OBJECTIVE: To assess the incidence of problems requiring reprogramming of atrioventricular pacemakers in a long-term follow-up, and also the causes for this procedure. METHODS: During the period from May '98 to December '99, 657 patients were retrospectively studied, An actuarial curve for the event reprogramming of the stimulation mode was drawn. RESULTS: The follow-up period ranged from 12 to 178 months (mean = 81 months). Eighty-two (12.4%) patients underwent reprogramming of the stimulation mode as follows: 63 (9.5%) changed to VVI,(R/C); 10 (1.5%) changed to DVI,C; 6 (0.9%) changed to VDD,C; and 3 (0.5%) changed to DOO. The causes for the reprogramming were as follows: arrhythmia conducted by the pacemaker in 39 (37.6%) patients; loss of atrial sensitivity or capture, or both, in 39 (38.6%) patients; and microfracture of atrial electrode in 5 (4.9%) patients. The stimulation mode reprogramming free probability after 15 years was 58%. CONCLUSION: In a long-term follow-up, the atrioventricular pacemaker provided a low incidence of complications, a high probability of permanence in the DDD,C mode, and the most common cause of reprogramming was arrhythmia conducted by the pacemaker.